2013
DOI: 10.5267/j.msl.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Investigating different cultural factors on establishment of knowledge management in educational organization

Abstract: Knowledge management plays an essential role on developing efficient systems in educational systems. However, there are different factors influencing the success of knowledge management. In this paper, we present an empirical study to measure the impact of six cultural based factors including management support, organizational affiliation, employee participation in decision-making, staff welfare organization and establishment, adaptation of new policies and organizational and internal organizational climate on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, the study did not provide any meaningful relationship between concentration and flexibility with organizational learning capability. Makhsousi et al (2013) presented an empirical investigation to measure the effect of six cultural based factors including management support, organizational affiliation, employee participation in decision-making, staff welfare organization and establishment, adaptation of new policies and organizational and internal organizational climate on establishment of knowledge management. They reported that management support, staff welfare organization and internal organizational climate were among the most important factors while other component did not represent any significance on knowledge management implementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study did not provide any meaningful relationship between concentration and flexibility with organizational learning capability. Makhsousi et al (2013) presented an empirical investigation to measure the effect of six cultural based factors including management support, organizational affiliation, employee participation in decision-making, staff welfare organization and establishment, adaptation of new policies and organizational and internal organizational climate on establishment of knowledge management. They reported that management support, staff welfare organization and internal organizational climate were among the most important factors while other component did not represent any significance on knowledge management implementation.…”
Section: Introductionmentioning
confidence: 99%
“…There are literally various factors impacting the success of knowledge management. Makhsousi et al (2013) presented a study to measure the effect of six cultural based factors including management support, organizational affiliation, employee participation in decision-making, staff welfare organization and establishment, adaptation of new policies and organizational and internal organizational climate on establishment of knowledge management in some educational organizations in Iran. They reported that management support, staff welfare organization and internal organizational climate were among the most influential factors while other components did not represent any important impact on knowledge management implementation.…”
Section: Introductionmentioning
confidence: 99%